Urban Riverside Area Development Study : (Case Study: Bah Bolon River, Pematang Siantar City) - Henry Swasta Sidabutar; Abdi Sugiarto; Cut Nuraini (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Urban riverbank areas are strategic spaces that hold ecological, social, cultural, and economic significance. In Pematang Siantar City, the Bah Bolon River has the potential to be developed as a sustainable urban ecotourism corridor. However, its current condition is marked by environmental degradation, infrastructure limitations, and poor spatial utilization. This study aims to identify development strategies that integrate environmental conservation, community-based tourism, and urban revitalization through placemaking and sustainable planning. This research adopts a qualitative descriptive approach focusing on the Bah Bolon River area in Pematang Siantar City. Data were collected through field observations, in-depth interviews with stakeholders, documentation review, and literature studies. The analysis involved descriptive mapping, SWOT analysis, community preference surveys, and land suitability assessments. Findings revealed that three key river segments—RINDAM I/BB area, Jalan Diponegoro–Jalan Jenderal Sudirman corridor, and the Quan Im Temple zone—exhibit varying levels of potential for ecotourism, cultural heritage, and public green space development. Key issues include pollution, informal land use, weak coordination, and insufficient infrastructure. Development opportunities include white-water rafting, thematic parks, spiritual reflection gardens, and creative economic zones. The study proposes an integrated riverbank development strategy, encompassing spatial zoning, ecological restoration, tourism infrastructure, community empowerment, and regional branding. It recommends the establishment of a multi-sector management agency, master planning, and cross-stakeholder collaboration to transform Bah Bolon River into a sustainable, inclusive, and resilient urban corridor.